GAMBARAN PELAKSANAAN KEGIATAN USAHA KESEHATAN GIGI SEKOLAH (UKGS) DAN SKOR PLAK MURID (Studi pada Sekolah Dasar dan Sederajat di Wilayah Kerja Puskesmas Padangsari Kota Semarang) - Diah Ajeng Pratiwi; Henry Setyawan Susanto; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Caries and periodontal disease are among the most prevalent oral health problems. It is caused by plaque. The highest caries prevalence in Central Java is in Semarang City. SDHP in primary school is dental health service program which aims to maintain and improve oral and dental health for students. The SDHP activities amounted to 8 activities, include: Teachers training, little doctor training, oral health education, toothbrushing program, emergency treatment, screening, referral system, and basic dental services. The aim of this research was to obtained an overview of an activities of SDHP and plaque score. The method of this research was cross-sectional study design. The samples 141 students were taken by proportional simple random sampling. The result showed students’s plaque score from schools with 6 activities of SDHP have an average 34,43, students’s plaque score from schools with 7 activities have an average 29,92, and students’s plaque score from schools with 8 activities have an average 29,78. The conclution indicates schools that implement all program of SDHP have a better plaque score.